Alleviatory efficacy of achillea millefolium L. in etoxazole-mediated toxicity in allium cepa L - Zeynep Şule Topatan; Tuğçe Kalefetoğlu Macar; Oksal Macar; Emine Yalçin; Kültiğin Çavuşoğlu; Ali Acar; Fatih Kutluer (Scientific Reports)
Abstract The application of pesticides may adversely impact a variety of non-target organisms. The use of side-effect-free herbal remedies to protect against the toxicity of harmful pesticides such as etoxazole has gained attention in recent times. The current study aimed to reveal the potential mitigating efficacy of Achillea millefolium L. extract against etoxazole toxicity in Allium cepa L. A. cepa bulbs in the control group were applied with tap water, while bulbs in the treatment groups were applied with etoxazole at dose of 0.5 m/L and two different doses of A. millefolium extract (200 mg/L and 400 mg/L). The impact of the treatments on certain parameters was evaluated. The molecular docking analysis was employed to investigate the potential interactions of etoxazole with DNA species, DNA topoisomerases, tubulin proteins, glutamate-1-semialdehyde aminotransferase, and protochlorophyllide reductase. The phenolic profile of A. millefolium was assessed. Etoxazole exposure reduced rooting percentage, root length, weight gain, mitotic index, and levels of chlorophyll a and chlorophyll b. Conversely, etoxazole treatment led to an increase in chromosomal aberrations and micronuclei occurrence. The most frequently observed chromosomal aberrations induced by etoxazole, which serve as bioindicators of genotoxicity, were fragment, vagrant chromosome, sticky chromosome, unequal chromatin distribution, bridge, reverse polarization, and vacuolated nucleus. The levels of malondialdehyde and antioxidant enzyme (superoxide dismutase and catalase) activities were also elevated. Epidermis cell damage, flattened cell nucleus, thickened cortex cell wall, and thickened conduction tissue were the meristematic cell disorders triggered by etoxazole. Molecular docking studies showed that etoxazole can interact directly with DNA, tubulins, and the enzymes mentioned above. A. millefolium extract was found to contain a substantial quantity of phenolic compounds. A. millefolium extract, when co-administered with etoxazole, attenuated all toxic effects of etoxazole dose-dependently. In conclusion, A. millefolium may potentially serve as a reliable pharmacological shield against the toxicity of pesticides in non-target organisms.